(untitled)
There is no doubt that for religious and scientific personalities; literary; Historic importance in our modern literature ©The modern poet reconstructs the past according to a contemporary human vision that reveals human concernshis suffering; His ambitions and dreams, and this is self-evident that our poets in the modern era are influenced by personalitiesreligious in general and the missionary personality embodied in the Messenger (©8) in particular; As the presence of thisThe personality in the modern poem constitutes a rich semantic field for what it stores in the religious history of the Arabs. and politician zAnd the social is one of the connotations that ignite the memory and move the hidden reservoirs in the Arab self. Dealing with this personality requires real awareness of it. Because it is a rich source that stores suggestive energiesable to move feelings and sensations; It is able to keep up with the data of reality with all its burdenscontrasts This is what makes it contain many contents; distant connotations; and implied gestures. And among those indications that we are trying to stand on (the symbol